Disposable e-cigarettes and their nicotine delivery, usage pattern, and subjective effects in occasionally smoking adults - Christin Falarowski; Elke Pieper; Andrea Rabenstein; Nadja Mallock-Ohnesorg; Nestor Burgmann; Klaas Franzen; Marcus Gertzen; Gabriele Koller; Dennis Nowak; Anna Rahofer; Benedikt Rieder; Gabriel Roselli de Oliveira Pinto Kise; et al. (Scientific Reports)
Abstract New disposable e-cigarettes are popular, especially among young people. This study aimed to assess their addictive potential by examining puffing behaviors, subjective effects, and conducting laboratory investigations in an experimental setting. Single-center, four-arm, crossover study. Laboratory setting in Munich (LMU-University Hospital), Germany. Eighteen occasionally cigarette-smoking adults aged 19–28. Two disposable e-cigarettes of the same brand (strawberry-kiwi/ tobacco flavored) were tested with a cigarette and a conventional pod e-cigarette as comparators. Usage was ad libitum for 5 min (or the duration of smoking one cigarette) while puffing topography was recorded. Distributed over 30 min blood samples for nicotine plasma concentrations were drawn and hemodynamic parameters and subjective effects assessed. Nicotine delivery of disposable e-cigarettes (Cmax strawberry-kiwi: 7.1 ng/ml, tobacco: 6.9 ng/ml) was similar to the cigarette (8.1 ng/ml) and higher than for the pod e-cigarette (3.1 ng/ml). The nicotine plasma increase in the first minute was the fastest for disposable e-cigarettes. Tmax for the disposable e-cigarettes (strawberry-kiwi: 5 min, tobacco: 6 min) was reached faster than for the cigarette (8 min). Compared to the pod e-cigarette (6 min), tmax was reached faster with the disposable e-cigarette tobacco. Total nicotine uptake was the lowest for the pod e-cigarette. Puffing behavior differed between e-cigarettes and the cigarette and slightly between both disposable e-cigarettes. Satisfaction and motivation to consume the product again were higher for disposables with a slight preference for strawberry-kiwi flavor. New disposable e-cigarettes hold great addictive potential for young people unestablished in smoking. Besides conducting further research, it is crucial to observe usage trends and strengthen regulations. Trial registration number: DRKS00030978. Date of registration: 21.02.2023.